A reassessment of the interaction between complement C3d and complement receptor CD21 SCR1-2 - Tso, C (2012)
Biophysical characterisation of protein – ligand interactions can provide vital information to dissect complex biochemical binding mechanisms. C3d has been shown to interact with a number of different protein ligands, namely CD21 SCR1-2, S. aureus Efb-C, S. aureus Ehp, S. aureus Sbi and complement regulatory protein factor H. Although much is known about the relationship of C3d and CD21 in the induction of humoral immunity, the structural aspects of this interaction remained controversial until very recently. The aim of this thesis was to gain a detailed understanding of the C3d/CD21 SCR1-2 interaction using different biophysical methods and to identify potential low molecular weight inhibitors of the interaction. A crystal structure of the C3d/CD21 complex solved by Szakonyi et al. in 2001 indicated the C3d binding site on CD21 was in the SCR2 domain. It did not agree with mutagenesis studies and recent NMR titration experiments show that only residues from the SCR1 domain of CD21 appear to mediate binding under physiologically relevant ionic strength. In the current work, NMR was employed to monitor ligand binding to C3d and to provide residue specific information that reflects a physiologically relevant binding mode to complement the crystallographic model solved by van den Elsen and Isenman in 2011. Microcalorimetric analysis on the site-directed mutagenesis studies also supported a model of hydrophobically- and electrostatically-driven protein-protein interaction for C3d and CD21 SCR1-2. Complement C3d forms a non-specific thioester linkage with antigen, which then binds to CD21 SCR1-2 and coligates with membrane immunoglobulin of the B cell receptor. While the interactions triggers B cell activation and hence the production of antibody under normal circumstances, it has been demonstrated that the interactions also lead to undue B cell activation and auto-antibody production. There is a well established collagen-induced arthritis (CIA) mouse model to support the significance of C3d and CD21 in disease susceptibility. To this end, a high-throughput SPR-based screening platform was set up to screen a fragment library against C3d, so as to identify low molecular weight compounds that could serve as a starting point for drug development programme. Unfortunately, the work did not yield C3d-binding inhibitors and future work could include screening large fragment libraries that are designed to target protein-protein interfaces.